2014
DOI: 10.1371/journal.pone.0102097
|View full text |Cite|
|
Sign up to set email alerts
|

Zinc Regulates Meiotic Resumption in Porcine Oocytes via a Protein Kinase C-Related Pathway

Abstract: Zinc is an extremely important trace element that plays important roles in several biological processes. However, the function of zinc in meiotic division of porcine oocytes is unknown. In this study, we investigated the role of zinc during meiotic resumption in in vitro matured porcine oocytes. During meiotic division, a massive release of zinc was observed. The level of free zinc in the cytoplasm significantly increased during maturation. Depletion of zinc using N, N, N′, N′-tetrakis (2-pyridylmethyl) ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…The amount of Zn 2+ in the oocyte increases during maturation and can regulate the timing of meiotic exit in mammalian oocytes [18]. This increase in the level of Zn 2+ during oocyte maturation has also been reported in pigs [30]. It was suggested that the release of Zn 2+ from FBXO43, a cytostatic factor with a Zn 2+ binding domain, relieves APC/C from FBXO43-mediated inhibition, thus initiating the degradation of MPF [20].…”
Section: Discussionmentioning
confidence: 95%
“…The amount of Zn 2+ in the oocyte increases during maturation and can regulate the timing of meiotic exit in mammalian oocytes [18]. This increase in the level of Zn 2+ during oocyte maturation has also been reported in pigs [30]. It was suggested that the release of Zn 2+ from FBXO43, a cytostatic factor with a Zn 2+ binding domain, relieves APC/C from FBXO43-mediated inhibition, thus initiating the degradation of MPF [20].…”
Section: Discussionmentioning
confidence: 95%
“…Follicles that were 3–6 mm in diameter were aspirated. Cumulus-oocyte complexes (COCs) that were surrounded by a minimum of three cumulus cells were selected for culture [ 27 ]. In brief, the COCs were washed three times in TL-HEPES supplemented with 0.1% polyvinyl alcohol (PVA, w/v) and 0.05 g/L gentamycin.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA extraction and cDNA synthesis were performed as previously described [ 28 ]. Briefly, mRNA was extracted from 10 blastocysts using Dynabeads mRNA Direct Kit (Dynal Biotech ASA, Oslo, Norway) followed by routine cDNA synthesis by reverse transcription (RT) of RNA using an oligo(dT) 12–18 primer and SuperScript Reverse Transcriptase (Invitrogen) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%